2000
DOI: 10.1021/jp9928255
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopy (XAS) Study of the Hydration Structure of Yttrium(III) Cations in Liquid and Glassy States:  Eight or Nine-Fold Coordination?

Abstract: An extensive X-ray absorption spectroscopy study has been carried out on 0.005 to 2.0 molal YBr 3 ‚6H 2 O aqueous solutions in liquid and glassy states to determine the solvation structure of the yttrium(III) cations in aqueous dilute and concentrate solutions. The existence of a symmetric polyhedron of water molecules around yttrium(III) cations at 2.35 Å, as well as the absence of contact Y-Br ion pairs, in all of the investigated solutions was deduced from the EXAFS analysis. The existence of a multiple ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 42 publications
8
78
0
Order By: Relevance
“…40 In this respect the study of XANES can provide useful complementary information as XANES is extremely sensitive to the stereochemical details of the absorbing site, i.e., overall symmetry, interatomic distances, and bond angles, offering better capabilities than a direct EXAFS analysis for the determination of the coordination polyhedron around the absorbing atom. [41][42][43] …”
Section: A Xanes: Qualitative Analysismentioning
confidence: 99%
“…40 In this respect the study of XANES can provide useful complementary information as XANES is extremely sensitive to the stereochemical details of the absorbing site, i.e., overall symmetry, interatomic distances, and bond angles, offering better capabilities than a direct EXAFS analysis for the determination of the coordination polyhedron around the absorbing atom. [41][42][43] …”
Section: A Xanes: Qualitative Analysismentioning
confidence: 99%
“…At present, the energy-dependent Hedin-Lundqvist ͑HL͒ complex potential 14,15 is the most widely used in ab initio XANES calculations. 16 However, it has been reported that in several cases, the energy-dependent Dirac-Hara ͑DH͒ exchange potential shows the best agreement to the experimental data, [17][18][19][20] although this assignment is not free of controversy. [22][23][24][25] As a result, the choice of the ECP among the usual scattering potential set, ranging from real X ␣ to complex Hedin-Lundqvist, becomes one of the most important steps in obtaining a good reproduction of the experimental spectra.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, we have very recently shown the singular behavior of x-rayabsorption spectra of Cu͑II͒ ions in nitrogen-coordinating square-planar complexes, 24 which shows a double channel for the absorption process due to two competitive final states. From this starting point and based upon previous experience in XANES computations of metal cations ͓Ni͑II͒, 25 Y͑III͒, 26 Cr͑III͒, and Rh͑III͒ ͑Ref. 27͔͒ and single anions, 28 we carried out an unbiased approach taking into account all the recently proposed structures for the Cu͑II͒ aquaion.…”
Section: Introductionmentioning
confidence: 99%